[PP.15.20] COST-EFFECTIVENESS OF RENAL DENERVATION COMPARED TO ANTIHYPERTENSIVE DRUG THERAPY IN TRUE RESISTANT HYPERTENSION: WE THINK IT OVER!. (September 2017) - Mazza, A.; Dell'avvocata, F.; Cardaioli, P.; Michielan, F.; Fiorini, F.; Gattazzo, D.; Compostella, A.F.; Contato, E.; Schiavon, L.; Ramazzina, E.
Abstract : Objective: Although the failure of the SYMPLICITY-3 trial in reaching its primary efficacy end-point, the catheter-based renal sympathetic denervation (RDN) remains the only tool to improve blood pressure (BP) control in patient with true resistant hypertension (RH). In the Veneto region, RDN is authorized only in two specialized centers, but in selected cases, is also performed in hospitals organized in the so-called Hub-model. Patients with RH are at a high risk for developing serious cardiovascular events increasing the global health costs. In this study, we assess cost-effectiveness and short-term clinical benefits of RDN. Figure. No caption available. Design and method: A 48-years old male, with a history of hypertension dated for over 10 years was annually admitted to our department for high BP levels not controlled by therapy until 7 anti-hypertensive drugs. The search for a cause of secondary hypertension revealed no clues. He was diabetic, overweight, with stage-3 of chronic renal disease and had multiple organ damage. At the last admission, BP averaged 226/128 mmHg and his medications were: amlodipine 20 mg, Ramipril 10 mg, spironolactone 25 mg, furosemide 50 mg, doxasozine 8 mg daily. 24h-ambulatory BP measurement (Figure 1A) confirmed RH. Patient underwent to RDN procedure using a third generation SpyralTM catheter, a device that is associated with a reduced procedural time, contrast use and radiation exposure. RDN was performed without complications, and after 48 h BP lowered up to 50 mmHg with 3 antihypertensive drugs (Figure 1B). Medical records of the 10 years before the last hospitalization were collected, and on medical DRG the global costs for RH management has been calculated and compared with the cost of the RDN procedure. Results: RDN therapy resulted in an increase on health benefit both for BP control and pharmacological treatment, so that patient stopped taking 4 anti-hypertensive drugs. In 10 years of admissions, the global health costs of hypertension management reached more than 57.000 Euro compared to the about 6, 000 Euro of the RDN procedure. Conclusions: RDN offers a meaningful and cost-effective alternative for achieving BP control, where traditional combination of antihypertensive pharmacologic strategies, have been proven to be ineffective.